Enrichment of provitamin A content in wheat (Triticum aestivum L.) by introduction of the bacterial carotenoid biosynthetic genes CrtB and CrtI - Wang, Cheng (Oxford University Press, 2014)

(untitled)
Carotenoid content is a primary determinant of wheat nutritional value and affects its end-use quality. Wheat grains contain very low carotenoid levels and trace amounts of provitamin A content. In order to enrich the carotenoid content in wheat grains, the bacterial phytoene synthase gene (CrtB) and carotene desaturase gene (CrtI) were transformed into the common wheat cultivar Bobwhite. Expression of CrtB or CrtI alone slightly increased the carotenoid content in the grains of transgenic wheat, while co-expression of both genes resulted in a darker red/yellow grain phenotype, accompanied by a total carotenoid content increase of approximately 8-fold achieving 4.76 μg g(–1) of seed dry weight, a β-carotene increase of 65-fold to 3.21 μg g(–1) of seed dry weight, and a provitamin A content (sum of α-carotene, β-carotene, and β-cryptoxanthin) increase of 76-fold to 3.82 μg g(–1) of seed dry weight. The high provitamin A content in the transgenic wheat was stably inherited over four generations. Quantitative PCR analysis revealed that enhancement of provitamin A content in transgenic wheat was also a result of the highly coordinated regulation of endogenous carotenoid biosynthetic genes, suggesting a metabolic feedback regulation in the wheat carotenoid biosynthetic pathway. These transgenic wheat lines are not only valuable for breeding wheat varieties with nutritional benefits for human health but also for understanding the mechanism regulating carotenoid biosynthesis in wheat endosperm.